3D Carbon−Metal Oxide Composite Electrodes on Graphite‐Coated Stainless Steel Substrate as a High‐Performance Anode for Lithium‐Ion Batteries. Issue 12 (14th July 2021) - Mamidi, Suresh; Potphode, Darshna; Pathak, Anil D.; Sharma, Chandra S.
Abstract : 3D microelectrodes are known to offer significant advantages compared with conventional thin‐film electrodes due to their large surface area and shorter diffusion lengths. However, the direct use of 3D microelectrodes on bare stainless steel (SS) causes low rate capabilities, poor cycling performance, and safety concerns. Herein, these issues are addressed by designing 3D microelectrodes on the graphite‐coated substrate with deposition of metal‐organic framework (MOF)‐derived nanostructured cobalt oxide petals at the base of the microelectrodes array. In this electrode configuration, graphite coating serves as an electrical interface between the microelectrodes and substrate, which lowers the resistance by providing efficient electron‐conducting pathways. The cobalt oxide facilitates Li‐ion diffusion and enhances the storage capability by conversion redox reactions. As an anode material, this 3D composite electrode delivers outstanding performance with a discharge capacity of 913 mAh g −1 at 100 mA g −1 current density even after 200 cycles. Furthermore, a diffusion‐limited model using the finite element method is developed to investigate the time‐dependent Li‐ion transport across 3D microelectrodes. The computational study demonstrates the advantages of 3D carbon microelectrode morphology over the conventional planar electrodes. The excellent cyclic stability with outstanding specific capacities confirms the potential applicability of this novel electrode for high‐performance lithium‐ion batteries. Abstract : Herein, 3D hard carbon microelectrodes on graphite‐coated substrates are integrated with a nanostructured cobalt oxide material. This electrode configuration synergistically improves the electrochemical performance by combining the different storage mechanisms such as insertion/intercalation and electrochemical redox reactions. Furthermore, the first‐principle calculation‐based density functional theory is conducted to understand the interaction of lithium ion with the electrode material.